Antagonism Trichoderma harzianum Rifai in Suppresing the Intensity of Antraknosa (Colletotrichum capcisi Sydow.) Disease - Yenny Muliani; Lilis Irmawatie; Siti Mariyam Sukma; Rafika Ratik Srimurni; Ida Adviany; Debby Ustari; Mia Nurul Milani (Fakultas Sains dan Teknologi, UIN Walisongo Semarang, 2022)
Cayenne pepper (Capsicum frutescens L.) is a horticultural plant that has high economic value and contains nutrients that the body needs. Cayenne pepper is one of the leading national horticultural commodities, so it is necessary to increase the production of cayenne pepper appropriately. The obstacle that is often faced in the production of cayenne pepper is the disruption of the production of cayenne pepper caused by the attack of anthracnose disease. Anthracnose disease or fruit rot caused by the fungus Colletotrichum capcisi Sydow can result in yield losses ranging from 20-90%. Trichoderma harzianum Rifai. is a soil saprophytic fungus that naturally can be used as a biological agent, because it has antagonism against pathogens in the form of competition for space and nutrients, mycoparasites and antibiosis. The experimental results in the laboratory showed that the biological agent Trichoderma harzianum Rifai was able to suppress the development of anthracnose disease.